2023
DOI: 10.1136/bcr-2022-252636
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus cerebellitis without skin manifestations in an immunocompetent adult

Abstract: The varicella zoster virus (VZV) is a ubiquitous, neurotropic pathogen capable of reactivation from sensory ganglion cells to cause dermatomal herpes zoster infection, alongside a range of pathologies within the central nervous system. The presence of VZV cerebellitis without skin manifestations, however, is exceedingly rare in immunocompetent adults.We report a case of VZV cerebellitis in an immunocompetent woman in her 70s, in the absence of a rash. The patient presented with a 2-week history of progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The study on the pathogenesis of PHN found that the VZV lurking in DRG proliferated, destroyed nerve axons, and caused nerve tissue damage [16]. These damaged sensory nerves produce abnormal nerve impulses, which continue to be input through DRG, resulting in increased pain sensitivity of peripheral and central nerves [7]. In addition to conventional drug treatment, minimally invasive treatment of PHN has also been widely recognized, which can relieve pain and improve the quality of life and is widely used in the treatment of postherpetic neuralgia [24].…”
Section: Discussionmentioning
confidence: 99%
“…The study on the pathogenesis of PHN found that the VZV lurking in DRG proliferated, destroyed nerve axons, and caused nerve tissue damage [16]. These damaged sensory nerves produce abnormal nerve impulses, which continue to be input through DRG, resulting in increased pain sensitivity of peripheral and central nerves [7]. In addition to conventional drug treatment, minimally invasive treatment of PHN has also been widely recognized, which can relieve pain and improve the quality of life and is widely used in the treatment of postherpetic neuralgia [24].…”
Section: Discussionmentioning
confidence: 99%